TRANSFORMASI KURIKULUM DI PESANTREN PADA ERA ABAD 21 - Tentiasih, Septyana (Universitas Muhammadiyah Ponorogo, 2024)
Education transformation in Indonesia continues to grow rapidly as the times progress. Many educators, especially in pesantren institutions, complain about this, especially in classical pesantren (salafiyah), there are still many institutions that use the pesantren curriculum with traditional learning methods. The purpose of this research is to find out the extent of curricular transformation in pesantren in the 21st century. The research method used in this research is to use a qualitative approach with the type of library research. The result of this study is that gradually the boarding school has used a modern curriculum and is not lagging behind with the changing times, especially in the era of globalization.